Stress, mental and physical health and the costs of health care in German high school students - Eppelmann, Lena; Parzer, Peter; Salize, Hans Joachim; Voss, Elke; Resch, Franz; Kaess, Michael (European child & adolescent psychiatry, 2020)
Stress is a mind-body phenomenon, which affects both mental and physical health and is highly relevant to the health care system. Yet, knowledge on the costs of stress and related health problems in adolescence is missing. The present study addresses this gap by investigating direct health care costs in relation to stress, mental health problems and physical health in high school students. The sample comprised 284 pupils from four schools in Heidelberg (mean age 16.75 ± 0.64 years, 59.64% female). Self-reported health care utilization and medication intake within 1 month were translated into costs. We established correlative associations of the dichotomized overall costs (no vs. any) with stress, mental health problems and physical health within generalized structural equation models. In particular, mental health problems and physical health were examined as mediators of the association between stress and costs. An increase of stress by 1 SD corresponded increased chances for costs by OR 1.39 (Odds Ratio; 95% CI  0.13-0.53, p = 0.001). When mediators were analysed separately, both mental and physical health (problems) fully mediated the association. Yet, when examined together, only mental health problems acted as a mediator. Our results indicate the health economic relevance of stress-related mental health problems in high school students. The finding is meant to set the stage for further cost-of-illness studies of stress and related health problems, as well as economic evaluations. Longitudinal research is needed to allow conclusions on directionality.